Бодончир мунхаг хэмээхийн учир - Лхагвадорж, Б. (Historia Mongolarum, 2009)
The author attempts to put toward a proposal in this academic paper, about Bodanchir who is sayed that senior ancestor of Chinggis khan, Alungoo’s youngest son who conceived by solar of heaven and sky and revealing what the reason he is noted that ’foolish" in Secret History of the Mongols.